Ladybug Girl and the Bug Squad - Soman, David; Davis, Jacky, 1966- (New York : Dial Books for Young Readers, 2011)
When Lulu invites her friends from the Bug Squad--all dressed up as insects--to come over for a play date, she wants everything to go just as she has planned.
"Companion to: Ladybug Girl"--Cover.
AD620
Accelerated Reader
Keywords: Play; Fiction; Cooperativeness; Fiction; Play -- Fiction; Cooperativeness -- Fiction; Play; Fiction; Cooperativeness -- Fiction; Play -- Fiction